Efficacy of a novel large-cell Niti-S stent with a slim delivery system for hilar biliary obstruction: a preliminary study. (31st December 2022) - Sugimoto, Mitsuru; Takagi, Tadayuki; Suzuki, Rei; Konno, Naoki; Asama, Hiroyuki; Sato, Yuki; Irie, Hiroki; Ishizaki, Yuto; Akatsuka, Hidenobu; Nakamura, Jun; Takasumi, Mika; Hashimoto, Minami; et al.
Abstract: Objectives: The large-cell Niti-S stent is useful for multiple stenting in patients with malignant hilar biliary obstruction (MHBO). Recently, a novel uncovered self-expandable metallic stent (USEMS) (a Niti-S large-cell SR slim delivery system) was developed. In this study, we aimed to evaluate the efficacy of this USEMS slim delivery system in MHBO patients. Materials and methods: Outcomes related to USEMS placement, the clinical course, and the period to recurrent biliary obstruction (RBO) were evaluated in MHBO patients who received multiple USEMSs with the Niti-S large-cell SR slim delivery system. Results: Twenty-two MHBO patients underwent the placement of multiple USEMSs, including the novel slim-delivery stent. Six patients had a past history of upper gastrointestinal reconstruction (Billroth I: 1, Billroth II: 4, Roux-en-Y: 1). The number of USEMSs placed in each patient was 2-6. Three procedures were reinterventions. The new slim delivery system was placed as the first stent in ten patients and as an additional stent in the remaining patients. Seven patients were drained using only Niti-S large-cell SR slim delivery stents. The technical and clinical success rates were both 100%. Conclusions: Placing multiple USEMSs in patients with a past history of abdominal surgery or in reintervention is difficult. Although difficult cases were included in this study, stent-in-stent placement with the novel Niti-S large-cell SR slim delivery system was useful in treating MHBO patients. In addition, this novel stent might be the first choice for MHBO patients. KEY MESSAGES: Endoscopic multistenting for MHBO is challenging. In addition, reintervention or multistenting for MHBO patients with a past history of abdominal surgery becomes more difficult. The novel Niti-S large-cell SR slim delivery USEMS is useful as an additional stent because the delivery system is thin and suitable for a 0.025 guidewire. In addition, the novel stent is of the braided type and has a large mesh. Therefore, the novel stent is expected to have strong radial force and can be used as the first SEMS. The Niti-S large-cell SR slim delivery stent is long enough to be used in patients with upper gastrointestinal reconstruction. Although this study included patients with reintervention or a past history of upper gastrointestinal reconstruction, the technical success rate of multiple stenting for MHBO patients was 100%. The slim-delivery stent might overcome several difficulties of endoscopic multistenting.